The Impact of the Entrepreneurship Promotion Programs and the Social Networks on the Sustainability Entrepreneurial Motivation of Engineering Students - Catalina Rus-Casas (Sustainability, 2020)
This paper presents the results of three academic courses in which Entrepreneurship Promotion Programs (EPP) have been developed for engineering students at the University of Jaén. This study describes the activities and how they have been promoted using the social networks Facebook and Twitter. Grytics for Analytics software was used for monitoring Facebook activity. The use of these tools has also allowed the collaborative development of the Engineering degree competencies related to sustainability and entrepreneurship through the Materials Science disciplines. The study is based on questionnaires before and after the EPP which involved a sample of 459 engineering students. The Kaiser–Meyer–Olkin test, Kolmogorov–Smirnov test and Pearson’s correlation were used. The questionnaires show which factors have the strongest influence on the intention to undertake entrepreneurial activity. Motivation (MO), personal requirements (PR), perception of the environment (PE) and the background requirements (BR) were the factors considered. The statistical study shows that PE and PR have a strong influence on MO. Finally, through the study before and after the EPP, the success of the activities and the use of social networks have been demonstrated. The results indicate that the activities of the EPP influence the perception of the environment and the motivation of the engineering students. However, the personal requirements are not affected by the activities.